Optimizing Fine Motor Skills in 5-6 Year Old Children Through a Play-While-Learning Approach - Nurfaizah; Litakun Karimah; Nova Triana; Susi Susanti; Siti Muntamah (EDUJAVARE: International Journal of Educational Research, 2026)
This study was motivated by the low fine motor skills of children aged 5–6 years in kindergarten, such as difficulties in holding writing tools properly, cutting along patterns, and pasting objects neatly. Fine motor skills are an essential aspect of early childhood development, particularly related to hand-eye coordination and school readiness (Sujiono, 2017; Santrock, 2018). The purpose of this study was to optimize children's fine motor skills through a learning-through-play approach. This research used classroom action research based on the Kemmis and McTaggart model, which includes planning, action, observation, and reflection stages (Kemmis et al., 2014). The study was conducted in a kindergarten in Way Kanan Regency with 15 children from group B as research subjects. Data collection techniques were carried out through observation and documentation (Sugiyono, 2019). The results showed an improvement in children's fine motor skills in each cycle of learning. In the initial observation, only 33% of children reached the expected development criteria. After the implementation of actions in cycle I, the percentage increased to 60%, and further improved to 87% in cycle II. These results indicate that the learning-through-play approach can improve the fine motor skills of children aged 5–6 years, in line with previous studies highlighting the importance of play-based activities in child development (Whitebread et al., 2017). Therefore, this approach can be an effective learning strategy to stimulate fine motor development in kindergarten children.